Arachnoid Cyst—Institutional Experience - Singaravelu, Madhan; Ramakrishnan, Selvaraj; Gopalakrishnan, Lakhmipathy (Indian Journal of Neurosurgery, 2019)
Background Arachnoid cysts are benign, non-neoplastic fluid collections within the arachnoid mater layer of the meninges. The etiology and significance of arachnoid cysts are poorly understood. Although they frequently represent incidental findings on central nervous system imaging, a wide variety of conditions have been attributed to their presence. The aim of this study is to ascertain the clinical presentation, location, and clinical course of patients with arachnoid cysts in the institution.Methods The authors analyzed the clinical presentation, radiologic images, and clinical course of 16 patients presented over a period of 6 months from August 2017 to January 2018.Results Of these 16 patients, 11 were adults and 5 were pediatric patients. Of these, seven were female and the remaining nine were male. Three patients presented with seizures, seven with headache, two with developmental delay, one with hydrocephalus, one with giddiness, one with hard of hearing, and one with bulging posterior fontanelle. Of these, 6 underwent surgery and 10 were managed conservatively.Conclusion Arachnoid cysts (non-neoplastic lesions) that produce symptoms through mass effect and obstructive hydrocephalus need surgical management, whereas a large percentage of cysts that are asymptomatic can be managed conservatively. The various surgical options available are marsupialization, cystoperitoneal shunt, ventriculoperitoneal (VP) shunt, and endoscopic fenestration. Microsurgery and endoscopy both allow for rapid decompression of the cyst and restoration of cerebrospinal fluid (CSF) circulation, whereas shunting tends to produce greater reduction in cyst size. Timing of presentation also decides upon the treatment options. Patients presenting late after the establishment of neurocognitive decline may not benefit from surgery and can be managed conservatively. A detailed genetic study may aid in the evolution of newer prevention and management options. Currently, most pediatric neurosurgeons prefer to avoid shunting, if possible. However, treatment paradigms are operator dependent and produce comparable outcomes.
Keywords: arachnoid cyst; non-neoplastic lesion; marsupialization